Validity of intraoperative imageless navigation (Naviswiss) for component positioning accuracy in primary total hip arthroplasty: protocol for a prospective observational cohort study in a single-surgeon practice. Issue 10 (5th October 2020) - Ektas, Nalan; Scholes, Corey; Ruiz, Alejandro M; Ireland, John
Abstract : Introduction: Optimal outcomes in total hip arthroplasty (THA) are dependent on appropriate placement of femoral and acetabular components, with technological advances providing a platform for guiding component placement to reduce the risk of malpositioned components during surgery. This study will validate the intraoperative data captured using a handheld imageless THA navigation system against postoperative measurements of acetabular inclination, acetabular version, leg length and femoral offset on CT radiographs. Methods and analysis: This is a prospective observational cohort study conducted within a single-centre, single-surgeon private practice. Data will be collected for 35 consecutive patients (>18 years) undergoing elective THA surgery, from the research registry established at the surgeon's practice. The primary outcome is the agreement between intraoperative component positioning data captured by the navigation system compared with postoperative measurements using CT. A total of ten CT scans will be reassessed for interobserver and intraobserver reliability. The influence of patient and surgical factors on the accuracy of component position will also be examined with multivariable linear regression. Ethics and dissemination: Ethics approval for this study was provided through a certified ethics committee (Bellberry HREC approval number 2017-07-499). The results of this study will be disseminated through peer-reviewed journals and conference presentations. Trial Registration: Australian and New Zealand Clinical Trials Registry (ANZCTR) Trial ID: ACTRN12620000089932.